Visitantes florais de Erythrina crista-galli L. e Erythrina falcata Benth (Leguminosae: faboideae) na região urbana de Santa Maria, Rio Grande do Sul, Brasil - Costa, Raimunda Alice Coimbra Vieira (2006)
Erythrina crista-galli L. and Erythrina falcata Benth. are the only two native species of corticeira from RS State. From 2004 to 2005, floral visitors, possible pollinators and phenology of those two species were studied at urban region of Santa Maria. On 42h of observations, 2750 visitors were registered on E. crista-galli. Apidae bees, Trigona spinipes (Fabricius, 1793) and Apis mellifera (Linnaeus, 1758) were the most frequent, being the probable pollinators, followed by wasps, ants, flies, beetles and butterflies. Besides insects, hummingbirds of the Trochilidae family were observed: Chlorostilbon aureoventris (d Orbigny and Lafresnaye, 1838), Amazilia versicolor (Vieillot, 1818) and Melanotrochilus fuscus (Vieillot, 1817). E. crista-galli flourishes from October to December. The anthesis is diurnal and lasts 5 days. On 40h of observations, 1238 floral visitors were registered on E. falcata, belonging to the same taxonomic groups registered for the previous species. The hummingbirds were the most frequent floral visitors and were considered pollinators of this species. E. falcata flourishes from September to November. The anthesis is diurnal and lasts 4 days. Handmade pollination tests results showed that E. crista-galli and E. falcata are autocompatible. The use of these two plant species is suggested as conservation strategy for pollinators native fauna species at urban and forestry environments.